BRAIN TUMOR DIAGNOSIS USING NANO DIGITAL TOPOLOGY - K.Shakilaja; K.Bhuvaneswari (Utilitas Mathematica, 2025)
In this paper, a Nano topological boundary approach is introduced for the identification of brain tumor in digital images.